Construction Monitoring and Numerical Simulation of Water-Rich Tuff Soft Rock Tunnel. Issue 1 (February 2020) - Chen, Fangliang; Zeng, Kaihua; Li, Xuejun; Xu, Manqing; Dai, Hongtao
Abstract: With the rapid development of China's high-speed railway construction, many difficulties have been encountered, and many difficulties and challenges have been encountered. Usually, there are safety accidents such as excessive deformation of the surrounding rock that causes serious intrusion, and even serious flooding, which not only restricts the construction period, Caused significant economic losses. The main reasons for these problems are insufficient understanding of the deformation mechanism of tunnel surrounding rocks, especially water-rich soft rock tunnels, and the lack of targeted control measures. This article takes the widely distributed tuffs in Zhejiang as an example. The tunnel deformation monitoring and measurement work can be used to grasp the dynamic evolution law of the surrounding rock. After the tunnel is excavated, the surrounding clearance of the surrounding rock and the settlement of the vault are determined. The key basis of process accuracy, the monitoring results are used to guide the next stage of construction and predict the deformation law of the surrounding rock in front of the palm face. At the same time, a finite element numerical model is established based on the surrounding rock structure of the tunnel to analyze the displacement and stress changes of the surrounding rock during the tunnel excavation process.